Pengaruh Philanthropy Disclosure terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Pemoderasi - Monita, Erdina; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 23 No 2 (2018), 2018)
High profitability can affect the number of philanthropy done by the company so as to increase value of the firm. Philanthropy disclosure provides a positive image in the eyes of society so that value of the firm increased by the price of its shares. This study aims to test and provide empirical evidence of the influence of philanthropy disclosure on value of the firm with profitability as a moderating variable. This research was conducted at state-owned company listed on BEI year 2014-2016. The number of samples taken as many as 45 companies, with purposive sampling method. Data collection method in this research is nonprobability sampling. Data analysis technique used is Moderating Regression Analysis (MRA). The results of the analysis found that philanthropy disclosure has a positive and significant effect on firm value. Profitability can strengthen the influence of philanthropy disclosure on corporate value.